Genetic structure of the Azores Islands : a study using 15 autosomal short tandem repeat loci - Santos, Cristina (Array, 2009)
Abstract: The Azores archipelago (Portugal), located in the Atlantic Ocean, 1,500 km from the European mainland, is formed by nine islands of volcanic origin. The relative position of these islands allows the definition of three geographical groups: Eastern, Central and Western. Previous studies of the Azores using Short Tandem Repeats (STRs) have highlighted differences in the frequencies of several loci, when compared to Mainland Portugal or Madeira Island. Furthermore, linkage disequilibrium (LD), described for Azorean samples has been tentatively explained as reflecting the presence of genetic sub-structuring in the archipelago. To provide information concerning the genetic profile of the Azores Islands and to evaluate the presence of substructuring we have determined the allelic frequencies of 15 autosomal STR loci, using the AmpFlSTR® Identifiler™ Kit, in representative samples from the Azorean Islands. Either considering the Azores as a whole, or analysing by island all the loci were in conformity with Hardy-Weinberg equilibrium. Average gene diversity ranged from 0.7669 in Corvo to 0.7972 in Terceira Island. Allelic independence between loci, tested for the global sample, detected significant LD (after correction for multiple tests) for pairs D21S11/D7S820 and D3S1358/D5S818. The exact test of population differentiation, combining the information of the 15 markers analysed, revealed significant differences between the three groups of islands, and between islands. Inter-island analysis reinforces the previous data that suggested the existence of sub-structuring in the Azores archipelago. Moreover, the data generated by this study can be used in a future forensic genetic database of the Azores after the appropriate enlacement of sample size by island, preventing, in that way, misinterpretations caused by population substructuring and small sample sizes